Bulbophyllum trongsaense (Orchidaceae: Epidendroideae: Dendrobieae), a new species from Bhutan - Gyeltshen, Phub; Gurung, Dhan Bahadur; Kumar, Pankaj (Phytotaxa, 2020)
Bulbophyllum trongsaense is described as a new species from Trongsa district of Bhutan. Detailed morphological description, distribution, phenology, ecology and colour photographs are provided along with comparison with B. amplifolium to which it shows closest affinity.